Repeated measures of implementation variables - Fixsen, Dean L.; Van Dyke, Melissa K.; Blase, Karen A. (Frontiers in Health Services, 2023)
It is commonly acknowledged that implementation work is long-term and contextual in nature and often takes years to accomplish. Repeated measures are needed to study the trajectory of implementation variables over time. To be useful in typical practice settings, measures that are relevant, sensitive, consequential, and practical are needed to inform planning and action. If implementation independent variables and implementation dependent variables are to contribute to a science of implementation, then measures that meet these criteria must be established. This exploratory review was undertaken to “see what is being done” to evaluate implementation variables and processes repeatedly in situations where achieving outcomes was the goal (i.e., more likely to be consequential). No judgement was made about the adequacy of the measure (e.g., psychometric properties) in the review. The search process resulted in 32 articles that met the criteria for a repeated measure of an implementation variable. 23 different implementation variables were the subject of repeated measures. The broad spectrum of implementation variables identified in the review included innovation fidelity, sustainability, organization change, and scaling along with training, implementation teams, and implementation fidelity. Given the long-term complexities involved in providing implementation supports to achieve the full and effective use of innovations, repeated measurements of relevant variables are needed to promote a more complete understanding of implementation processes and outcomes. Longitudinal studies employing repeated measures that are relevant, sensitive, consequential, and practical should become common if the complexities involved in implementation are to be understood.